Some Issues of the healthcare financing model - Archaia, Ketevan ("Intercultural Dialogues" Transactions, 2023)
Assessing the economic effectiveness of pricing in healthcare and studying problems is one of the important issues in the field of healthcare. World experience has shown the need to solve problems in the field of pricing, optimal costs will ultimately be reflected in pricing and the development of the quality of healthcare. The government should be focused not on reducing health care costs, but towards growth and optimization, which should naturally be in line with the quality of services. All of this can be achieved through economic development. Some aspects of funding, existing health indicators, the importance of climbing the DRG system, and the positive impact of the OLG model in relation to healthcare financing issues are also discussed.